New sustainable fashion business models: “the coworking” case study - Barcellos, L. F. (2019)
The current fashion scenario presents unsustainable practices and business models, which are focused on the mass market, reducing the costs and stimulating hyperconsumption. In opposition to this, new sustainable fashion business models are emerging with high ethical attitudes and more conscious with the future of the planet. Thus, it becomes relevant to explore sustainable fashion business models. In this context, the main goal of this article is to identify new existent models and the concepts that underlie them. The method used was the exploratory research, through case analysis, to stimulate the understanding of the theme. The results embrace coworking spaces, which are identified by the concepts they involve and how a new business model can contribute to a more sustainable fashion system.